Registering Parapsychological Experiments - Watt, Caroline (Journal of Scientific Exploration, 2013)
A webpage for registering parapsychological experiments has been implemented by the Koestler Parapsychology Unit (KPU) at the University of Edinburgh, with Jim Kennedy advising on the development of the registry. The value of study registration for a controversial area such as parapsychology has been mentioned many times over the years. Prospective registration of experiments provides a database for research synthesis that is not subject to possible reporting or publication biases. Registration also increases confidence by providing clear evidence that the key hypotheses and analyses were planned prior to conducting the experiment. Among other benefits, registration should be of value to editors and reviewers during the publication process. Registration of experiments is a well-established practice in medical research and enhances the credibility of a study. The KPU registry webpage is at: http://www.koestler-parapsychology.psy.ed.ac.uk/TrialRegistry.html. We expect that other options for study registration will become available in the future. Our intention is for the KPU registry webpage to also serve as a resource that provides information about other registration options as they become available.